Novel nanocomposite automotive temperature sensing technology - Kelly, Andrew; Impey, Susan A.; Mitsev, Petar; Nicholls, John R. (Cranfield University Press, 2013)
In recent years, automotive emissions legislation has been introduced and is rapidly becoming more stringent. With alternative vehicular propulsion methods far from becoming mainstream reality, leading automotive providers have intensified efforts in the direction of reducing the harmful footprint of their products. This is being accomplished via smaller, more optimally designed internal-combustion engines. A crucial means to that end is exhaust gas temperature monitoring and control. To enable such control, a mass-produced sensor, capable of operating reliably in the harsh automotive combustion environment, comprising a broad spectrum of high temperatures, severe shocks and a chemically aggressive ambient, has been used widely in the past decade, with performance demands growing constantly in line with advances in engine performance. This paper presents a technology overview of the potential of novel nano composite sensor design and manufacture using materials in an innovative way towards industrialising such a sensing solution. The presented sensor design implements the state-of-the-art in thick and thin film technology incorporating nano materials for improved strength, fabrication and performance properties.
Keywords: Thin Film Technology; Thick film technology; Exhaust Gas Temperature Sensing